A Study on the Poetics of Justice: the Discourse of Resistance In Selected Indian Fiction: Exploring the Intersection of Politics and Aesthetics in Indian Fiction (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The present study regards the political and the poetic(or aesthetic) as inseparable in the space of literature. The political projectof the quest for justice is also, at the same time, a poetic project thatrecasts the orders of vision and visibility, indeed the entire range and scopeof the relationship between human sensibility and the world. Recent Indianfiction, as the analysis in the following pages demonstrates, exemplifies thefinest melding of the political and the aesthetic in a veritable poetics ofjustice articulated as a vibrant, layered and many-sided discourse ofresistance. The word resistanceis derived from the Latin root word resister, meaning tostand against, which denotes a slow but insistent, often invisible butenduring strategy that has the potential to dislodge the dominant structures,if not dismantle them. Resistance may involve a re-interpretation of thehegemonic biases that regulate the identities of the subaltern groups and thussilence those groups.